Asturias en el bienio Constitucional (1812-1814) - Carantoña Álvarez, Francisco (Estudios humanísticos. Geografía, historia y arte, 1988)
This paper maintains that asturian members of the "Cortes de Cadiz" were elected in a fairly representative way, in accordance with the provisions of a previous regulation by the "Junta Central". Nevertheless, the Constitution of 1812 was introduced in the Princedom and for two years people lived under the constitutional order. It met the strongest opposition in the Roman Catholic Church, especially after the suppression of the Inquisition at the beginning of 1813.